Development of E-Book Textbooks in Injury Prevention and Treatment Subjects Based on Media Flip Book Maker - Danang Prama Dhani; Rian Triprayogo; Ida Zubaida; Sendy Mohamad Anugrah; Andy Widhiya Bayu Utomo (STKIP Muhammadiyah Kuningan, 2022)
This study has the objectives of knowing the results of identifying learning outcomes problems, reviewing and planning products, knowing the consequences of expert trials, the results of small group trials and large group trials, and knowing the effects of product effectiveness tests from the E-Book Textbook for the Prevention and Treatment course. Injury-Based Media Flip Book Maker. This study uses a research development/RnD (research and development) approach. The data source for this research is IKOR Untirta students class of 2018-2021. The data collection techniques used were: a) Interview techniques, b) Questionnaire techniques, c) Test techniques, and d) Observation techniques. Qualitative and quantitative approaches were chosen as data analysis techniques in this study. The research results in the first stage showed that the final percentage of the evaluation of academic experts was 80.2%, with the results of assessments from practitioners, namely 84.2%, so an average of 82.2% was obtained from the expert test. And the two experts have stated that the contents of the product design are feasible for further trials in the limited/small group trial stage. From the table above, the initial product in each chapter has an average rating of 79% for ease of understanding, 69% for attractiveness, and 84% for usefulness. And it needs improvement at several points in specific chapters to get better results from the initial product. In the large group trial stage, each chapter has an average rating of 88% for ease of understanding, 87% for attractiveness, and 90% for usefulness. The points in each chapter no longer require significant improvement because the researcher assesses from the table above that each chapter has obtained satisfactory results on the product effectiveness test. The conclusion from this study is that the methods that have been used so far have not been able to make students understand PPC material fully; product preparation is prepared using systematic steps referring to the current P2SIKI curriculum; in the expert test it is stated that the contents of the product design are feasible for testing the next stage, the results of the small group and large group trials need to be carried out several evaluations which are completed at the product revision stage. Finally, the effectiveness test results show a significant effect of using e-book textbooks based on flip book maker media on student understanding in injury prevention and treatment courses.